Assessment of the current state of health of the population of Ukraine - L.R. Krynychko (Економіка, управління та адміністрування, 2020)
The article provides a detailed description of the state of health of the population of Ukraine. Special attention is paid to the demographic situation in Ukraine in comparison with the leading regions of the World Health Organization. The article describes the current state of health of the world's population by regions, namely in the African region, in the regions of the Americas, in the region of Southeast Asia, in the European region, in the Eastern Mediterranean region, in the western Pacific region. The World Bank assessed the state of maternal and child mortality in the regions of the World Health Organization. Viral morbidity (new cases of HIV infection, tuberculosis incidence, malaria incidence, prevalence of hepatitis B surface antigen (HBsAg) among children under 5, the number of people in need of treatment for NTD) in the regions of the World Health Organization was estimated. The results of the study of the population health index of Ukraine are described. The World Health statistics is analyzed in order to determine the actual state of health care in Ukraine and its closest neighbours. The study determined the state of Health Protection of the population of Ukraine and its closest neighbours: Moldova, Romania, Hungary, Slovakia, Poland, Belarus, Russia, Georgia. The life expectancy of the population of Ukraine and its closest neighbours is analyzed. Maternal and child mortality were estimated in the study countries based on World Bank statistics. Economic aspects of the state of health are reflected and measures are proposed to improve the current situation.